Legal nature of the Supreme Court resolutions (Ius Novum, 2020)
The article presents the issue of the legal nature of the Supreme Court resolutions. The nature is a matter of argument in the doctrine. There are three diverse viewpoints on this issue. According to one of them, ‘the Supreme Court resolutions are judgments’. Another stance is that ‘the Supreme Court resolutions constitute a separate group; however, they are not court judgments that concern the subject matter of a trial because they do not adjudicate directly on its subject matter’. The third opinion is that ‘the Supreme Court resolutions passed in accordance with Article 441 § 1 CPC and resolving legal issues do not belong to the category of judgments’. The analysis conducted in the article results in a conclusion that the Supreme Court resolutions do not constitute judgments in the precise sense, that are imperative in nature, that adjudicate on the subject matter of a particular trial with regard to both procedural and incidental issues, but they are the Supreme Court’s procedural decisions that resolve a legal issue requiring fundamental interpretation of a statute or resolve a legal issue in a situation when doubts have been raised concerning the interpretation of provisions of law being grounds for issued judgments.
Keywords: Supreme Court; judicial supervision; non-instance-related supervision; judgment; sentence; decision; resolution